One Kind Special Gauss Sums and their Mean Square Values - Jianhong Zhao; Jiejie Gao (Journal of Mathematics)
In this paper, we introduce one kind special Gauss sums; then, using the elementary and analytic methods to study the mean value properties of these kind sums, we obtain several exact calculating formulae for them.